Transparent double-sided pressure-sensitive adhesive sheet and pressure-sensitive adhesive sheet laminate
A transparent double-sided adhesive sheet with a (meth)acrylic copolymer and UV absorber addresses UV degradation and adhesion challenges in thin image display devices by providing effective UV absorption and photo-curable properties for reliable adhesion.
Patent Information
- Application Number
- JP2020199579
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-02-29
- Filing Date
- 2020-12-01
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2036-11-24
AI Technical Summary
Existing transparent double-sided adhesive sheets used in image display devices face issues with UV degradation, leading to deterioration and decomposition when exposed to long-term UV radiation, which affects adhesion and reliability. Additionally, the thinning of image display device components makes it challenging to achieve both UV absorption and reliable adhesion.
A transparent double-sided adhesive sheet comprising a single layer or multiple adhesive layers formed from a resin composition containing a (meth)acrylic copolymer, a crosslinking agent, a photopolymerization initiator with a high extinction coefficient at 405 nm, and an ultraviolet absorber. This composition allows for primary adhesion followed by photo-curing for secondary adhesion, enhancing UV absorption and foaming resistance.
The adhesive sheet achieves effective UV absorption and photo-curing, ensuring reliable adhesion and resistance to foaming and peeling, even on components prone to UV degradation. This solution addresses the challenges of thinning image display devices by providing a robust adhesive layer with enhanced UV protection.
Smart Images

Figure 0007666913000001 
Figure 0007666913000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent double-sided pressure-sensitive adhesive sheet that can be used as a component for constituting image display devices such as personal computers, mobile terminals (PDAs), game consoles, televisions (TVs), car navigation systems, touch panels, and pen tablets. [Background technology]
[0002] In recent years, in order to improve the visibility of image display devices, the gap between an image display panel such as a liquid crystal display (LCD), a plasma display panel (PDP), or an electroluminescence display (ELD) and a protective panel or touch panel member placed on the front side (viewing side) of the image display panel has been filled with an adhesive to suppress reflection of incident light and outgoing light from a displayed image at the air layer interface.
[0003] As a method for filling such gaps between components of an image display device with an adhesive, a method is known in which a liquid adhesive resin composition containing an ultraviolet-curable resin is filled into the gap and then cured by irradiating with ultraviolet light (Patent Document 1).
[0004] Also known is a method of filling gaps between components of an image display device with an adhesive sheet. For example, Patent Document 2 discloses a method in which an adhesive sheet that has been primarily crosslinked by ultraviolet light is attached to the components of an image display device, and then the adhesive sheet is irradiated with ultraviolet light through the components of the image display device for secondary curing.
[0005] Patent Document 3 discloses a method for filling gaps between components of an image display device using an adhesive sheet made of a hot melt type adhesive composition having a loss tangent of less than 1 at 25°C, the main component of which is a urethane (meth)acrylate with a weight average molecular weight of 20,000 to 100,000. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2010 / 027041 [Patent Document 2] Patent No. 4971529 [Patent Document 3] International Publication No. 2010 / 038366 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, when two components of an image display device are attached using an adhesive sheet made of an adhesive resin composition containing a base resin, a crosslinking agent, and an ultraviolet polymerization initiator, the two components of the image display device are primarily attached via the adhesive sheet, and then ultraviolet light is irradiated from the outside of one of the components of the image display device to UV-cure the adhesive sheet through the component of the image display device for secondary attachment. This method makes it possible to perform primary attachment while filling in any unevenness on the attachment surface, and also to further increase the adhesive reliability by finally curing the components. However, when such an ultraviolet-sensitive adhesive sheet is exposed to ultraviolet light for a long period of time, the adhesive sheet itself deteriorates, producing decomposition products that may cause foaming or peeling. Furthermore, some of the components of the image display device are susceptible to deterioration by ultraviolet light. In such cases, it is not possible to adhere two components of the image display device using the method described above. Furthermore, if the image display device components are ultraviolet absorbing, even if ultraviolet light is irradiated through the component, the ultraviolet light will not reach the adhesive sheet sufficiently, and therefore, even in such a case, it is not possible to adhere the two image display device components using the method described above.
[0008] On the other hand, as image display devices become thinner, new functions are being required for pressure-sensitive adhesive sheets. In order to prevent ultraviolet degradation of liquid crystals, organic EL elements, polarizing plates, etc., image display device components may be required to have an ultraviolet absorbing function, and this function has generally been ensured by polarizing plate protective films. However, as image display device components become thinner, polarizing plate protective films also become thinner, making it difficult to obtain sufficient ultraviolet absorbing function. Therefore, image display device components other than polarizing plate protective films, such as adhesives and pressure-sensitive adhesive sheets, are also required to have an ultraviolet absorbing function.
[0009] However, it is difficult to impart an ultraviolet absorbing function to the above-mentioned ultraviolet curing type adhesive sheet. On the other hand, unless a method is adopted in which the adhesive sheet is used to fill the unevenness of the adherend surface while being primarily adhered, and then the sheet is further cured and adhered secondarily, it is impossible to achieve both the step absorption property when the adherend surface of the adherend member has unevenness and the foaming resistance reliability after lamination.
[0010] Therefore, the present invention aims to provide a new transparent double-sided adhesive sheet that has ultraviolet light absorption function and can be further cured and used for secondary application after primary application using an adhesive sheet. [Means for solving the problem]
[0011] The present invention relates to a pressure-sensitive adhesive comprising a single layer or two or more layers of a pressure-sensitive adhesive layer formed from a pressure-sensitive adhesive resin composition containing a (meth)acrylic copolymer (A), a crosslinking agent (B), a photopolymerization initiator (C) having an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm, and an ultraviolet absorber (D), The transparent double-sided pressure-sensitive adhesive sheet contains at least a polyfunctional (meth)acrylate as the crosslinking agent (B), and the pressure-sensitive adhesive layer is photocurable. Effect of the Invention
[0012] The transparent double-sided adhesive sheet for image display of the present invention has an ultraviolet absorbing function, and furthermore, after the primary application using the adhesive sheet, it can be further light-cured for secondary application, so that it can achieve both step absorption when the surface to be adhered of the bonding member is uneven and foaming resistance reliability after bonding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An embodiment of the present invention will be described in detail below. However, the present invention is not limited to the embodiment described below.
[0014] <This adhesive sheet> A transparent double-sided pressure-sensitive adhesive sheet according to one embodiment of the present invention is a transparent double-sided pressure-sensitive adhesive sheet (referred to as "the pressure-sensitive adhesive sheet") made of a pressure-sensitive adhesive resin composition (referred to as "the pressure-sensitive adhesive composition") containing a (meth)acrylic copolymer (A), a crosslinking agent (B), a photopolymerization initiator (C) having an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm, and an ultraviolet absorber (D).
[0015] [(Meth)acrylic copolymer (A)] The (meth)acrylic polymer used as the base polymer of this pressure-sensitive adhesive sheet can have properties such as glass transition temperature (Tg) appropriately adjusted by the types and composition ratios of the acrylic and methacrylic monomers used to polymerize it, as well as the polymerization conditions.
[0016] The "base polymer" in this adhesive sheet means the resin that is the main component of this adhesive sheet. It does not specify a specific content. As a guideline, it is a resin that accounts for 50% or more by mass of the resin contained in this adhesive sheet, preferably 65% or more by mass, and more preferably 80% or more by mass (including 100% by mass). When there are two or more types of base polymer, the total amount of them corresponds to the above content.
[0017] Examples of the (meth)acrylic (co)polymer (A) include homopolymers of alkyl (meth)acrylates, as well as copolymers obtained by polymerizing a monomer component copolymerizable therewith. More preferred examples include copolymers containing, as monomer components, an alkyl (meth)acrylate and one or more monomers selected from a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an amino group-containing monomer, an epoxy group-containing monomer, an amide group-containing monomer, and other vinyl monomers that are copolymerizable therewith.
[0018] More specifically, examples of such copolymers include copolymers composed of one or more monomers selected from a linear or branched alkyl (meth)acrylate having 4 to 18 carbon atoms in the side chain (hereinafter also referred to as "copolymerizable monomer A"), a carboxyl group-containing monomer copolymerizable therewith (hereinafter also referred to as "copolymerizable monomer B"), a vinyl monomer (hereinafter also referred to as "copolymerizable monomer C"), a (meth)acrylate having 1 to 3 carbon atoms in the side chain (hereinafter also referred to as "copolymerizable monomer D"), and a hydroxyl group-containing monomer (hereinafter "copolymerizable monomer E").
[0019] Particularly preferred examples include (a) a copolymer composed of a monomer component including a copolymerizable monomer A, a copolymerizable monomer B and / or a copolymerizable monomer C, and (b) a copolymer composed of a monomer component including a copolymerizable monomer A, a copolymerizable monomer B and / or a copolymerizable monomer C, and a copolymerizable monomer D and / or a copolymerizable monomer E. Specifically, examples include a copolymer of copolymerizable monomers A and B, a copolymer of copolymerizable monomers A and C, a copolymer of copolymerizable monomers A, B and C, a copolymer of copolymerizable monomers A, B and D, a copolymer of copolymerizable monomers A, B and E, a copolymer of copolymerizable monomers A, B, D and E, a copolymer of copolymerizable monomers A, C and D, a copolymer of copolymerizable monomers A, C and E, a copolymer of copolymerizable monomers A, C, D and E, a copolymer of copolymerizable monomers A, B, C and D, a copolymer of copolymerizable monomers A, B, C and E, a copolymer of copolymerizable monomers A, B, C, D and E.
[0020] Examples of the "copolymerizable monomer A" include n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, t-butyl cyclohexyl (meth)acrylate, Examples of such acrylates include silyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, 3,5,5-trimethylcyclohexane (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0021] The copolymerizable monomer A is preferably contained in an amount of 30% by mass or more and 90% by mass or less of the total monomer components of the copolymer, more preferably 35% by mass or more or 88% by mass or less, and even more preferably 40% by mass or more or 85% by mass or less.
[0022] Examples of the "copolymerizable monomer B" include (meth)acrylic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, 2-(meth)acryloyloxyethylphthalic acid, 2-(meth)acryloyloxypropylphthalic acid, 2-(meth)acryloyloxyethylmaleic acid, 2-(meth)acryloyloxypropylmaleic acid, 2-(meth)acryloyloxyethylsuccinic acid, 2-(meth)acryloyloxypropylsuccinic acid, crotonic acid, fumaric acid, maleic acid, and itaconic acid. These may be used alone or in combination of two or more. In addition, "(meth)acrylic" means to include acrylic and methacrylic. Similarly, "(meth)acryloyl" means to include acryloyl and methacryloyl.
[0023] The above-mentioned "copolymerizable monomer C" may be a compound having a vinyl group in the molecule. Examples of such compounds include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 12 carbon atoms, functional monomers having functional groups such as a hydroxyl group, an amide group, and an alkoxyl alkyl group in the molecule, polyalkylene glycol di(meth)acrylates, vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl laurate, and aromatic vinyl monomers such as styrene, chlorostyrene, chloromethylstyrene, α-methylstyrene, and other substituted styrenes. These may be used alone or in combination of two or more.
[0024] The copolymerizable monomer B and the copolymerizable monomer C are contained in the total monomer components of the copolymer in an amount of 1.2 mass % to 15 mass % or less, and from the viewpoint of obtaining excellent adhesive properties, it is preferable that they are contained in an amount of 1.5 mass % or more or 10 mass % or less, and particularly 2 mass % or more or 8 mass % or less.
[0025] Examples of the "copolymerizable monomer D" include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, etc. These may be used alone or in combination of two or more. The copolymerizable monomer D is preferably contained in an amount of 0% by mass or more and 70% by mass or less of the total monomer components of the copolymer, more preferably 3% by mass or more or 65% by mass or less, and even more preferably 5% by mass or more or 60% by mass or less.
[0026] Examples of the "copolymerizable monomer E" include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0027] The copolymerizable monomer E is preferably contained in an amount of 0% by mass or more and 30% by mass or less in the total monomer components of the copolymer, more preferably 0% by mass or more or 25% by mass or less, and even more preferably 0% by mass or more or 20% by mass or less.
[0028] In addition to the above, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride, epoxy group-containing monomers such as glycidyl (meth)acrylate, α-ethyl glycidyl acrylate, and 3,4-epoxybutyl (meth)acrylate, amino group-containing (meth)acrylic acid ester monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate, amide group-containing monomers such as (meth)acrylamide, Nt-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, maleic acid amide, and maleimide, and heterocyclic basic monomers such as vinyl pyrrolidone, vinyl pyridine, and vinyl carbazole can also be used as necessary.
[0029] Specific examples of the (meth)acrylic (co)polymer include, for example, a monomer component (a) such as 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, isostearyl (meth)acrylate, butyl (meth)acrylate, ethyl (meth)acrylate, or methyl (meth)acrylate, and a monomer component (b) such as (meth)acrylic acid having a carboxyl group, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, 2-(meth)acryloyloxyethylphthalic acid, 2-(meth)acryloyloxypropylphthalic acid, 2-(meth)acryloyloxyethylmaleic acid, or 2-(meth)acryloyloxyethylmaleic acid. Examples of the monomer component (b) include 2-(meth)acryloyloxypropyl maleate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxypropyl succinate, crotonic acid, fumaric acid, maleic acid, itaconic acid, or the like, and a monomer component (c) having an organic functional group, or the like, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, monomethyl maleate, monomethyl itaconate, vinyl acetate, glycidyl (meth)acrylate, (meth)acrylamide, (meth)acrylonitrile, fluorinated (meth)acrylate, silicone (meth)acrylate, or the like, can be mentioned as a (meth)acrylic acid ester copolymer obtained by copolymerizing the monomer component (b) with an organic functional group, or the like, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, monomethyl maleate, monomethyl itaconate, vinyl acetate, glycidyl (meth)acrylate, (meth)acrylamide, (meth)acrylonitrile, fluorinated (meth)acrylate, silicone (meth)acrylate, or the like.
[0030] The mass average molecular weight of the (meth)acrylic (co)polymer is preferably 100,000 to 1,500,000, more preferably 150,000 or more or 1,300,000 or less, and even more preferably 200,000 or more or 1,200,000 or less.
[0031] When a high cohesive strength adhesive composition is to be obtained, the mass average molecular weight is preferably 700,000 to 1,500,000, particularly 800,000 or less, or 1,300,000 or less, from the viewpoint that the higher the molecular weight, the higher the cohesive strength obtained by the entanglement of molecular chains. On the other hand, when a high fluidity or stress relaxation adhesive composition is to be obtained, the mass average molecular weight is preferably 70,000 to 700,000, particularly 100,000 or more, or 600,000 or less. In addition, when a solvent is not used in forming an adhesive sheet or the like, it is difficult to use a polymer with a large molecular weight, so the mass average molecular weight of the acrylic copolymer is preferably 70,000 to 700,000, particularly 100,000 or more, or 600,000 or less, and particularly 150,000 or more, or 500,000 or less.
[0032] (Acrylic copolymer (A1)) An example of a preferred base polymer for the present pressure-sensitive adhesive sheet is a (meth)acrylic copolymer (A1) made of a graft copolymer having a macromonomer as a branch component.
[0033] When the adhesive sheet is constructed using the above-mentioned acrylic copolymer (A1) as a base resin, the adhesive sheet can exhibit self-adhesiveness while maintaining its sheet shape at room temperature, has hot-melt properties such that it melts or flows when heated in an uncrosslinked state, and can be photocured, and after photocuring, it can exert excellent cohesive strength to adhere. Therefore, when the acrylic copolymer (A1) is used as the base polymer of the present pressure-sensitive adhesive sheet, even in an uncrosslinked state, the sheet exhibits adhesiveness at room temperature (20°C), and also has the property of softening or becoming fluid when heated to a temperature of 50 to 90°C, more preferably 60°C or higher or 80°C or lower.
[0034] The glass transition temperature of the copolymer constituting the backbone component of the acrylic copolymer (A1) is preferably from -70 to 0°C. In this case, the glass transition temperature of the copolymer component constituting the trunk component refers to the glass transition temperature of a polymer obtained by copolymerizing only the monomer components constituting the trunk component of the acrylic copolymer (A1). Specifically, it means a value calculated by the Fox formula from the glass transition temperature and the composition ratio of the polymer obtained from the homopolymer of each component of the copolymer. The Fox formula is a calculated value obtained by the following formula, and can be obtained using the values described in Polymer Handbook (Polymer Handbook, J. Brandrup, Interscience, 1989). 1 / (273+Tg)=Σ(Wi / (273+Tgi)) [In the formula, Wi represents the weight fraction of monomer i, and Tgi represents the Tg (°C) of a homopolymer of monomer i.]
[0035] The glass transition temperature of the copolymer component constituting the backbone of the acrylic copolymer (A1) affects the flexibility of the pressure-sensitive adhesive sheet at room temperature and the wettability of the pressure-sensitive adhesive sheet to an adherend, i.e., the adhesiveness. Therefore, in order for the pressure-sensitive adhesive sheet to have appropriate adhesiveness (tackiness) at room temperature, the glass transition temperature is preferably -70°C to 0°C, and in particular -65°C or higher or -5°C or lower, and in particular -60°C or higher or -10°C or lower. However, even if the glass transition temperatures of the copolymer components are the same, the viscoelasticity can be adjusted by adjusting the molecular weight. For example, the copolymer component can be made softer by decreasing its molecular weight.
[0036] Examples of the (meth)acrylic acid ester monomer contained in the trunk component of the acrylic copolymer (A1) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and the like. ) acrylate, t-butylcyclohexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, isobornyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 3,5,5-trimethylcyclohexane acrylate, p-cumylphenol EO-modified (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like.In addition to these, hydroxyl group-containing (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate, which have hydrophilic groups or organic functional groups, (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxypropyl maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxypropyl succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, monomethyl itaconate, Also usable are carboxyl group-containing monomers such as butyl, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride, epoxy group-containing monomers such as glycidyl (meth)acrylate, α-ethyl glycidyl acrylate, and 3,4-epoxybutyl (meth)acrylate, amino group-containing (meth)acrylic acid ester monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate, amide group-containing monomers such as (meth)acrylamide, Nt-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone acrylamide, maleic acid amide, and maleimide, and heterocyclic basic monomers such as vinyl pyrrolidone, vinyl pyridine, and vinyl carbazole. In addition, various vinyl monomers copolymerizable with the above acrylic monomers or methacrylic monomers, such as styrene, t-butylstyrene, α-methylstyrene, vinyl toluene, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl propionate, alkyl vinyl ethers, hydroxyalkyl vinyl ethers, and alkyl vinyl monomers, can also be used appropriately.
[0037] The backbone component of the acrylic copolymer (A1) preferably contains a hydrophobic (meth)acrylate monomer and a hydrophilic (meth)acrylate monomer as structural units. When the backbone component of the acrylic copolymer (A1) is composed only of hydrophobic monomers, it is prone to whitening under heat and humidity. Therefore, it is preferable to also introduce a hydrophilic monomer into the backbone component to prevent whitening under heat and humidity.
[0038] Specifically, the backbone component of the acrylic copolymer (A1) may be a copolymer component obtained by random copolymerization of a hydrophobic (meth)acrylate monomer, a hydrophilic (meth)acrylate monomer, and a polymerizable functional group at the end of a macromonomer.
[0039] Here, examples of the hydrophobic (meth)acrylate monomer include n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, and nonyl (meth)acrylate. acrylate, isononyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and methyl methacrylate. Examples of hydrophobic vinyl monomers include vinyl acetate, styrene, t-butylstyrene, α-methylstyrene, vinyltoluene, and alkyl vinyl monomers.
[0040] Examples of the hydrophilic (meth)acrylate monomer include methyl acrylate, (meth)acrylic acid, tetrahydrofurfuryl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, and other hydroxyl group-containing (meth)acrylates, (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl male ... carboxyl group-containing monomers such as 2-(meth)acryloyloxypropyl maleate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxypropyl succinate, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; epoxy group-containing monomers such as glycidyl (meth)acrylate, α-ethyl glycidyl acrylate, and 3,4-epoxybutyl (meth)acrylate; alkoxy polyalkylene glycol (meth)acrylates such as methoxy polyethylene glycol (meth)acrylate; N,N-dimethylacrylamide; and hydroxyethylacrylamide.
[0041] (Branch component: macromonomer) The acrylic copolymer (A1) preferably contains a repeating unit derived from a macromonomer introduced as a branch component of the graft copolymer. A macromonomer is a polymer monomer having a terminal polymerizable functional group and a high molecular weight backbone component.
[0042] The glass transition temperature (Tg) of the macromonomer is preferably higher than the glass transition temperature of the copolymer component constituting the acrylic copolymer (A1). Specifically, since the glass transition temperature (Tg) of the macromonomer affects the heat melting temperature (hot melt temperature) of the pressure-sensitive adhesive sheet, the glass transition temperature (Tg) of the macromonomer is preferably 30°C to 120°C, and more preferably 40°C or higher or 110°C or lower, and even more preferably 50°C or higher or 100°C or lower. If the glass transition temperature (Tg) is within this range, excellent processability and storage stability can be maintained, and the polymer can be adjusted to hot melt at a temperature of approximately 50°C to 80°C by adjusting the molecular weight. The glass transition temperature of a macromonomer refers to the glass transition temperature of the macromonomer itself, and can be measured by a differential scanning calorimeter (DSC).
[0043] In addition, in order to maintain a physically crosslinked state in the pressure-sensitive adhesive composition at room temperature, where the branch components are attracted to each other, and to enable the physical crosslinks to be broken down and fluidity to be obtained by heating to an appropriate temperature, it is also preferable to adjust the molecular weight and content of the macromonomer. From this viewpoint, the macromonomer is preferably contained in the acrylic copolymer (A1) in a proportion of 5% by mass to 30% by mass, more preferably 6% by mass or more or 25% by mass or less, and even more preferably 8% by mass or more or 20% by mass or less. The number average molecular weight of the macromonomer is preferably 500 or more and less than 8,000, more preferably 800 or more or less than 7,500, and even more preferably 1,000 or more or less than 7,000. As the macromonomer, a generally produced one (for example, a macromonomer manufactured by Toagosei Co., Ltd.) can be appropriately used.
[0044] The high molecular weight backbone component of the macromonomer is preferably composed of an acrylic polymer or a vinyl polymer. Examples of the high molecular weight skeleton component of the macromonomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. acrylate, heptyl (meth)acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate acrylate, isobornyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 3,5,5-trimethylcyclohexane acrylate, p-cumylphenol EO modified (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, benzyl (meth)acrylate, hydroxyalkyl (meth)acrylate, (meth)acrylic acid, glycidyl (meth)acrylate, (meth)acrylamide, N,N-dimethyl (meth)acrylamide, (meth)acrylonitrile, alkoxyalkyl (meth)acrylate, alkoxypolyalkylene glycol (meth)acrylate, and various vinyl monomers such as styrene, t-butylstyrene, α-methylstyrene, vinyl toluene, alkyl vinyl monomer, alkyl vinyl ester, alkyl vinyl ether, and hydroxyalkyl vinyl ether, which may be used alone or in combination of two or more.
[0045] Examples of the terminal polymerizable functional group of the macromonomer include a methacryloyl group, an acryloyl group, and a vinyl group.
[0046] [Crosslinking agent (B)] Examples of the crosslinking agent (B) include crosslinking agents having at least one crosslinkable functional group selected from the group consisting of (meth)acryloyl groups, epoxy groups, isocyanate groups, carboxyl groups, hydroxyl groups, carbodiimide groups, oxazoline groups, aziridine groups, vinyl groups, amino groups, imino groups, and amide groups, and one or more of these may be used in combination. The crosslinkable functional group may be protected with a protecting group which can be removed.
[0047] Examples of such polyfunctional (meth)acrylates include 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerin di(meth)acrylate, glycerin glycidyl ether di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-Nonanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, bisphenol A polyethoxy di(meth)acrylate, bisphenol A polyalkoxy di(meth)acrylate, bisphenol F polyalkoxy di(meth)acrylate, polyalkylene glycol di(meth)acrylate, trimethylolpropane trioxyethyl (meth)acrylate, ε-caprolactone modified tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate Examples of the ultraviolet-curable polyfunctional monomers include acrylate, tris(acryloxyethyl)isocyanurate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol penta(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, di(meth)acrylate of hydroxypivalic acid neopentyl glycol adduct with ε-caprolactone, trimethylolpropane tri(meth)acrylate, alkoxylated trimethylolpropane tri(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate. Examples of the ultraviolet-curable polyfunctional monomers include polyester(meth)acrylate, epoxy(meth)acrylate, urethane(meth)acrylate, and polyether(meth)acrylate. Examples of the ultraviolet-curable polyfunctional monomers include polyfunctional acrylic oligomers such as polyester(meth)acrylate, epoxy(meth)acrylate, urethane(meth)acrylate, and polyether(meth)acrylate.
[0048] Among the above-mentioned polyfunctional (meth)acrylic acid ester monomers, from the viewpoint of improving the adhesion to the adherend and the effect of suppressing wet heat whitening, polyfunctional monomers or oligomers containing a polar functional group such as a hydroxyl group, a carboxyl group, an amide group, etc. are preferred. Among them, it is preferred to use a polyfunctional (meth)acrylic acid ester having a hydroxyl group or an amide group. From the viewpoint of preventing wet heat whitening, it is preferable that the (meth)acrylic acid ester copolymer (A1), i.e., the backbone component of the graft copolymer, contains a hydrophobic acrylate monomer and a hydrophilic acrylate monomer, and further, it is preferable to use a polyfunctional (meth)acrylic acid ester having a hydroxyl group as the crosslinking agent (B). In order to adjust the effects of adhesion, moist heat resistance, heat resistance, etc., a monofunctional or polyfunctional (meth)acrylic acid ester which reacts with the crosslinking agent (B) may be further added.
[0049] From the viewpoint of balancing the flexibility and cohesive strength of the pressure-sensitive adhesive composition, the content of the crosslinking agent (B) is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), and more preferably 0.5 parts by mass or more or 15 parts by mass or less, and even more preferably 1 part by mass or more or 13 parts by mass or less.
[0050] [Photopolymerization initiator (C)] The photopolymerization initiator (C) used in the present pressure-sensitive adhesive sheet functions as a reaction initiation assistant in the crosslinking reaction of the crosslinking agent (B), and is preferably one that generates radicals by irradiation with visible light, for example, light in the wavelength region of 380 nm to 700 nm, to become the starting point of the polymerization reaction of the base resin. However, it may be one that generates radicals only by irradiation with visible light, or one that generates radicals by irradiation with light in a wavelength region other than the visible light region.
[0051] From this viewpoint, it is particularly preferable that the photopolymerization initiator (C) has an absorption coefficient at a wavelength of 405 nm of 10 mL / (g·cm) or more, of which 15 mL / (g·cm) or more, and of which 25 mL / (g·cm) or more is particularly preferable. The absorption coefficient in the present invention corresponds to the absorbance at an optical path length of 1 cm when the photopolymerization initiator is dissolved in methanol at a concentration of 1 g / L.
[0052] Examples of photopolymerization initiators with an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-(4-methylbenzyl)-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, and bis(η 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide, thioxanthone, 2-chlorothioxanthanate Examples of photopolymerization initiators include 3-methylthioxanthone, 2,4-dimethylthioxanthone, anthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 1,2-octanedione, 1-(4-(phenylthio), 2-(o-benzoyloxime)), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-ethanone 1-(O-acetyloxime), camphorquinone, and triazine-based photopolymerization initiators. These may be used alone or in combination with two or more of them, or in combination with a photoinitiator with an extinction coefficient of less than 10 mL / (g cm) at a wavelength of 405 nm.
[0053] Photopolymerization initiators are broadly classified into two types based on the radical generation mechanism: cleavage-type photopolymerization initiators, which can generate radicals by cleaving and decomposing the single bond of the photopolymerization initiator itself, and hydrogen abstraction-type photopolymerization initiators, which form an exciplex between the photoexcited initiator and the hydrogen donor in the system and transfer the hydrogen from the hydrogen donor. Among these, the cleavage type photopolymerization initiator decomposes to another compound when generating radicals by light irradiation, and once excited, it no longer functions as a reaction initiator. For this reason, when the intramolecular cleavage type is used as the photopolymerization initiator (C) having an absorption wavelength in the visible light range, it is preferable compared to the case of using the hydrogen abstraction type, because after the adhesive sheet is crosslinked by light irradiation, the photoreactive photopolymerization initiator remains as an unreacted residue in the adhesive composition, which is less likely to cause unexpected changes over time in the adhesive sheet or promotion of crosslinking. In addition, regarding the coloring specific to the photopolymerization initiator, it is preferable because it becomes a reactive decomposition product, which no longer absorbs in the visible light range, and one that disappears in color can be appropriately selected. On the other hand, hydrogen abstraction type photopolymerization initiators do not produce decomposition products like cleavage type photopolymerization initiators during the radical generating reaction upon irradiation with active energy rays such as ultraviolet rays, and therefore are less likely to become volatile components after the reaction is completed, making it possible to reduce damage to the adherend.
[0054] Examples of the cleavage-type photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-(4-(2-hydroxyethoxy)phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-[4-{4-(2-hydroxy-2-methyl-propionyl)benzyl}phenyl]-2-methyl-propan-1-one, oligo(2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propanone), methyl phenylglyoxylate, 2-benzyl-2-dimethylamino-1- Examples of such compounds include (4-morpholinophenyl)butan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide, and derivatives thereof.
[0055] Among these, acylphosphine oxide photoinitiators such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide are preferred because they are cleavage-type photopolymerizable initiators that become decomposed products and lose color after the reaction. Furthermore, in view of compatibility with acrylic copolymers consisting of graft copolymers having macromonomers as branch components, it is preferable to use 2,4,6-trimethylbenzoyldiphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide, or the like as the photopolymerization initiator (C).
[0056] The content of the photopolymerization initiator (C) is not particularly limited. For example, it is preferably 0.1 to 10 parts by mass, more preferably 0.2 parts by mass or more or 5 parts by mass or less, and even more preferably 0.5 parts by mass or more or 3 parts by mass or less, based on 100 parts by mass of the (meth)acrylic copolymer (A). However, this range may be exceeded depending on the balance with other factors. The photopolymerization initiator may be used alone or in combination of two or more kinds.
[0057] [Ultraviolet absorber (D)] The ultraviolet absorber (D) may be any substance capable of absorbing ultraviolet light. As a guideline, it is preferable that the addition of the ultraviolet absorber (D) can increase the absorbance of the transparent double-sided pressure-sensitive adhesive sheet at a wavelength of 380 nm to 0.3 or more, preferably 0.5 or more, and more preferably 1 or more.
[0058] The absorbance at a wavelength of 380 nm can be calculated using the following formula. A 380 =-Log(T 380 / 100) A 380 : Absorbance at wavelength 380 nm T 380 :Transmittance (%) of transparent double-sided adhesive sheet at 380 nm
[0059] The ultraviolet absorber (D) is preferably one having one or more structures selected from the group consisting of a benzotriazole structure, a benzophenone structure, a triazine structure, a benzoate structure, an oxalanilide structure, a salicylate structure, and a cyanoacrylate structure. Among these, from the viewpoint of ultraviolet absorbing properties, those having one or more structures selected from the group consisting of a benzotriazole structure, a triazine structure, and a benzophenone structure are preferred. From the viewpoint of compatibility with the acrylic copolymer consisting of a graft copolymer having a macromonomer as a branch component, it is preferable to use a benzotriazole structure or a benzophenone structure as the ultraviolet absorbent (D).
[0060] The content of the ultraviolet absorber (D) is not particularly limited. For example, it is preferably contained in an amount of 0.01 to 10 parts by mass, more preferably 0.1 parts by mass or more or 5 parts by mass or less, and even more preferably 0.2 parts by mass or more or 3 parts by mass or less, based on 100 parts by mass of the (meth)acrylic copolymer (A). However, it may exceed this range depending on the balance with other factors.
[0061] From the viewpoint of absorbing ultraviolet rays and initiating photopolymerization in the visible light region excluding the ultraviolet rays, the ratio of the ultraviolet absorber (D) to 100 parts by mass of the photopolymerization initiator (C) is preferably 25 to 400 parts by mass, more preferably 50 parts by mass or more or 300 parts by mass or less, and even more preferably 80 parts by mass or more or 250 parts by mass or less. The ultraviolet absorbers can be used alone or in combination of two or more kinds.
[0062] [Other ingredients] The pressure-sensitive adhesive sheet may contain other known components that are incorporated in ordinary pressure-sensitive adhesive compositions, such as tackifier resins, antioxidants, light stabilizers, metal deactivators, rust inhibitors, antiaging agents, moisture absorbents, hydrolysis inhibitors, sensitizers, antistatic agents, defoamers, and inorganic particles. Furthermore, a reaction catalyst (such as a tertiary amine compound, a quaternary ammonium compound, or a tin laurate compound) may be appropriately contained as necessary.
[0063] [Preferable composition example] An example of a particularly preferred composition of the pressure-sensitive adhesive composition includes an acrylic copolymer consisting of a graft copolymer having a macromonomer as a branch component as the (meth)acrylic copolymer (A), a polyfunctional (meth)acrylic acid ester compound such as a bifunctional or trifunctional compound as the crosslinking agent (B), a cleavage-type photopolymerization initiator as the photopolymerization initiator (C), and an ultraviolet absorber having a benzotriazole structure or a benzophenone structure as the ultraviolet absorber (D). However, the composition is not limited to this.
[0064] [Layer structure] The pressure-sensitive adhesive sheet may be a single-layer sheet or a multi-layer sheet having two or more layers laminated together. When the present pressure-sensitive adhesive sheet is to be a multi-layer pressure-sensitive adhesive sheet, i.e., when forming a pressure-sensitive adhesive sheet having a laminated structure with an intermediate layer and an outermost layer, it is preferable that the outermost layer is formed from the present pressure-sensitive adhesive composition.
[0065] When the pressure-sensitive adhesive sheet has a multi-layer structure, the ratio of the thickness of each outermost layer to the thickness of the intermediate layer is preferably 1:1 to 1:20, and more preferably 1:2 to 1:10. It is preferable that the thickness of the intermediate layer is within the above range, since the contribution of the thickness of the adhesive layer in the laminate is not too large, and the intermediate layer is not too soft, which deteriorates workability in cutting and handling. Furthermore, if the outermost layer is in the above range, it is preferable since it will not be inferior in conformity to uneven or curved surfaces and it will be possible to maintain adhesive strength and wettability to the adherend.
[0066] [Sheet thickness] Regarding the thickness of this adhesive sheet, by making the sheet thinner it is possible to meet the demand for thinner walls. However, if the sheet is too thin, there is a possibility that, for example, if the adherend surface has unevenness, the sheet will not be able to adequately conform to the unevenness or will not be able to exert sufficient adhesive strength. From this viewpoint, the thickness of the present pressure-sensitive adhesive sheet is preferably 20 to 500 μm, more preferably 25 μm or more or 350 μm or less, and even more preferably 50 μm or more or 250 μm or less.
[0067] (characteristic) The ultraviolet transmittance (JIS K7361-1) of this pressure-sensitive adhesive sheet at a wavelength of 380 nm is preferably 50% or less, more preferably 30% or less, and even more preferably 10% or less.
[0068] <Adhesive sheet laminate> The pressure-sensitive adhesive sheet can be used alone as it is, or can be used by laminating it with other members.
[0069] (Present adhesive sheet laminate) For example, it is possible to form a pressure-sensitive adhesive sheet laminate (referred to as "the pressure-sensitive adhesive sheet laminate") by laminating a release film on one or both sides of the pressure-sensitive adhesive sheet.
[0070] In this case, it is preferable that one or both of the release films have a light transmittance of 40% or less for light with a wavelength of 410 nm or less. If at least one of the release films has a light transmittance of 40% or less for light with a wavelength of 410 nm or less, then by laminating the release film to the pressure-sensitive adhesive sheet, it is possible to effectively prevent photopolymerization from proceeding due to irradiation with visible light, even if the pressure-sensitive adhesive sheet contains a photopolymerization initiator (C) with an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm. From this viewpoint, it is preferable that one or both of the release films have a light transmittance for light having a wavelength of 410 nm or less of 40% or less, more preferably 30% or less, and even more preferably 20% or less.
[0071] Here, examples of release films having a light transmittance of 40% or less for light having a wavelength of 410 nm or less, that is, release films having the effect of partially blocking the transmission of visible light and ultraviolet light, include cast films or stretched films made of polyester-based, polypropylene-based, or polyethylene-based resins containing ultraviolet absorbers, which are coated with silicone resin for release treatment. Examples of multi-layer cast films or stretched films formed by molding a layer of resin not containing ultraviolet absorbers on one or both sides of a layer made of polyester-based, polypropylene-based, or polyethylene-based resin containing ultraviolet absorbers, are those coated with silicone resin on one side for release treatment. Examples of cast films or stretched films made of polyester-based, polypropylene-based, or polyethylene-based resins are those coated with a paint containing ultraviolet absorbers on one side to provide an ultraviolet absorbing layer, and then coated with silicone resin on the ultraviolet absorbing layer for release treatment. Examples of cast films or stretched films made of polyester-based, polypropylene-based, or polyethylene-based resins are those coated with a paint containing ultraviolet absorbers on one side to provide an ultraviolet absorbing layer, and then coated with silicone resin on the ultraviolet absorbing layer for release treatment. Examples of cast films or stretched films made of polyester-based, polypropylene-based, or polyethylene-based resins are those coated with a paint containing ultraviolet absorbers on one side to provide an ultraviolet absorbing layer, and then coated with silicone resin on the other side for release treatment. Another example is a laminate formed by laminating one side of a resin film made of a polyester-based, polypropylene-based, or polyethylene-based resin, one side of which has been release-treated, and the other side of a separately prepared resin film that has not been release-treated, via an adhesive layer or pressure-sensitive adhesive layer containing an ultraviolet absorber.
[0072] The release film may have other layers, such as an antistatic layer, a hard coat layer, or an anchor layer, if necessary. If the thickness of the release film is too thick, the cutting processability is poor, and if the thickness is too thin, the handling property is poor and the adhesive sheet may be easily dented. From this viewpoint, the thickness of the release film is preferably 20 μm or more and 300 μm or less, more preferably 25 μm or more or 250 μm or less, and even more preferably 38 μm or more or 200 μm or less. When a release film is laminated on both sides, it is preferable that one release film has a different thickness or peeling force from the other release film.
[0073] As a preferred configuration example, a surface protection film having a light transmittance of 40% or less for light having a wavelength of 410 nm or less may be laminated on one or both sides of the pressure-sensitive adhesive sheet laminate. By laminating a surface protection film with a light transmittance of 40% or less for light with a wavelength of 410 nm or less on at least one surface of the pressure-sensitive adhesive sheet laminate, it is possible to effectively prevent photopolymerization from progressing when irradiated with visible light, even if the pressure-sensitive adhesive sheet contains a photopolymerization initiator (C) with an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm. From this viewpoint, the surface protection film laminated on one or both sides of the present pressure-sensitive adhesive sheet laminate preferably has a light transmittance for light having a wavelength of 410 nm or less of 40% or less, more preferably 30% or less, and even more preferably 20% or less.
[0074] Here, as a surface protective film having a light transmittance of 40% or less for light having a wavelength of 410 nm or less, that is, a surface protective film having a function of partially blocking the transmission of visible light and ultraviolet light, for example, a laminated film having an ultraviolet absorbing layer formed by applying a slightly adhesive resin having removability to one side of a polyester-based, polypropylene-based, or polyethylene-based cast film or stretched film, and applying a paint containing an ultraviolet absorber to the other side can be mentioned. In addition, a polypropylene-based or polyethylene-based cast film or stretched film having a slightly adhesive resin having removability and containing an ultraviolet absorber to one side can be mentioned. In addition, a cast film or stretched film made of a polyester-based, polypropylene-based, or polyethylene-based resin containing an ultraviolet absorber can be mentioned, which is coated with a slightly adhesive resin having removability. In addition, a multilayer cast film or stretched film formed by forming a layer of a resin not containing an ultraviolet absorber on one or both sides of a layer made of a polyester-based, polypropylene-based, or polyethylene-based resin containing an ultraviolet absorber can be mentioned, which is coated with a slightly adhesive resin having removability to one side. In addition, a coating material containing an ultraviolet absorbent is applied to one side of a cast film or stretched film made of a polyester, polypropylene, or polyethylene resin to provide an ultraviolet absorbing layer, and a slightly adhesive resin having removability is applied on the ultraviolet absorbing layer. In addition, a coating material containing an ultraviolet absorbent is applied to one side of a cast film or stretched film made of a polyester, polypropylene, or polyethylene resin to provide an ultraviolet absorbing layer, and a slightly adhesive resin having removability is applied on the other side. In addition, a resin film made of a polyester, polypropylene, or polyethylene resin, one side of which is coated with a slightly adhesive resin having removability, and the other side of which is laminated with a resin film prepared separately, via an adhesive layer or adhesive layer containing an ultraviolet absorbent, can be mentioned. The surface protective film may have other layers, such as an antistatic layer, a hard coat layer, or an anchor layer, if necessary.
[0075] (Laminate for use in constructing the image display device) It is also possible to construct a laminate for constituting an image display device (referred to as "the laminate for constituting the image display device") by laminating two components for an image display device via the present pressure-sensitive adhesive sheet.
[0076] In this case, the two components for the image display device may be, for example, any one of the group consisting of a touch sensor, an image display panel, a surface protection panel, and a polarizing film, or a combination of two or more kinds.
[0077] Specific examples of the laminate for constituting the present image display device include structures such as release sheet / present adhesive sheet / touch panel, release sheet / present adhesive sheet / protective panel, release sheet / present adhesive sheet / image display panel, image display panel / present adhesive sheet / touch panel, image display panel / present adhesive sheet / protective panel, image display panel / present adhesive sheet / touch panel / present adhesive sheet / protective panel, polarizing film / present adhesive sheet / touch panel, polarizing film / present adhesive sheet / touch panel / present adhesive sheet / protective panel, etc. However, the laminate is not limited to these lamination examples. The above touch panel includes a structure in which a touch panel function is incorporated in a protection panel, and a structure in which a touch panel function is incorporated in an image display panel.
[0078] (This image display device) An image display device (referred to as "the image display device") can be constructed using the present pressure-sensitive adhesive sheet or the present laminate for constructing an image display device as described above. The present image display device can be, for example, a liquid crystal display, an organic EL display, an inorganic EL display, electronic paper, a plasma display, a microelectromechanical system (MEMS) display, or the like.
[0079] <Features and usage of this adhesive sheet> The adhesive sheet has an ultraviolet absorbing function and a curing property that allows it to be cured by irradiation with light of a wavelength other than the ultraviolet region, particularly visible light. By utilizing such properties of the adhesive sheet, a laminate for constituting an image display device can be produced, for example, as follows.
[0080] The adhesive composition is formed into a sheet (sheet preparation process), and then two components of an image display device are laminated via the adhesive sheet before photocuring (primary attachment process). Next, the adhesive sheet is photocrosslinked and cured by irradiating it with light containing light rays with wavelengths in the visible light region (secondary attachment process), thereby producing a laminate for use in constructing an image display device. The light containing light rays with wavelengths in the visible light range may also contain light in the ultraviolet range, i.e., light with wavelengths of 380 nm or less; however, when the laminated image display device components are susceptible to deterioration by ultraviolet light, it is preferable to irradiate the adhesive sheet with light rays that do not substantially contain light with wavelengths of 380 nm or less, i.e., visible light, to photocrosslink and harden the adhesive sheet (secondary adhesion process).
[0081] (Sheet manufacturing process) The pressure-sensitive adhesive composition can be formed into a sheet to produce the pressure-sensitive adhesive sheet. As a method for forming the present pressure-sensitive adhesive resin composition into a sheet, any currently known method can be adopted.
[0082] In this case, as described above, the present pressure-sensitive adhesive resin composition may be formed into a sheet-like film on the release film to produce the present pressure-sensitive adhesive sheet. The present pressure-sensitive adhesive resin composition may be formed into a sheet on a component of an image display device, and the present pressure-sensitive adhesive sheet may be laminated on the component of the image display device.
[0083] (Primary pasting process) If the present pressure-sensitive adhesive sheet has self-adhesive properties (tackiness), primary adhesion can be achieved simply by overlapping two image display device components with the present pressure-sensitive adhesive sheet interposed therebetween.
[0084] For example, if the pressure-sensitive adhesive sheet has an acrylic copolymer (A1) as the base polymer, which is a graft copolymer having a macromonomer as a branch component, not only can it maintain its sheet shape at room temperature while exhibiting self-adhesiveness, but also can have a suitable adhesiveness in an uncrosslinked state, for example, an adhesiveness that allows peeling (called "tackiness") in a normal state, i.e., near room temperature, which makes it easier to position the sheet when it is applied. Furthermore, since it can be melted or flowed when heated in an uncrosslinked state (hot melt property), the pressure-sensitive adhesive can be filled in a manner that conforms to uneven parts such as printing steps, and can be filled without generating air bubbles.
[0085] The lamination device used for lamination may be a known device, such as an electric heat press equipped with a heating plate, a diaphragm type laminator, a roll laminator, a vacuum laminator, a hand roll, or the like.
[0086] In addition, when the present pressure-sensitive adhesive sheet uses as a base polymer an acrylic copolymer (A1) consisting of a graft copolymer having a macromonomer as a branch component, it can provide excellent storage stability and cutting processability under normal conditions, i.e., at room temperature. Moreover, since it has self-adhesive properties (tackiness), it can obtain enough adhesiveness that it can be easily attached just by pressing the present pressure-sensitive adhesive sheet against an adherend, making it easy to position the adhesive material for application, and very convenient in terms of work. Furthermore, since it has excellent shape retention properties, it can be processed into any shape in advance, and therefore the adhesive sheet formed on a release film can be cut in advance to match the dimensions of the image display device components to be laminated. The cutting method in this case is generally punching with a Thompson blade, cutting with a super cutter or laser, and it is more preferable to half-cut while leaving a frame-like portion of the release film on either the front or back side so that the release film can be easily peeled off.
[0087] If the adhesive sheet has hot melt properties, i.e., the property of becoming soft or fluid when heated, even if the surface to be adhered is uneven, the adhesive sheet can be heated to conform to the unevenness and fill the unevenness without any gaps. In this case, the means for heating the pressure-sensitive adhesive sheet can be, for example, various thermostatic chambers, hot plates, electromagnetic heating devices, heating rolls, etc. In order to perform lamination and heating more efficiently, for example, an electric heating press, a diaphragm type laminator, a roll laminator, etc. are preferably used.
[0088] In this case, if the softening temperature of the pressure-sensitive adhesive sheet is 50° C. or higher, the processing characteristics and storage characteristics at room temperature can be sufficient. On the other hand, if the softening temperature of the pressure-sensitive adhesive sheet is 100° C. or lower, not only can thermal damage to the image display panel and front panel be suppressed, but also the pressure-sensitive adhesive sheet can be prevented from flowing too much and spilling out. Therefore, the softening temperature of the present pressure-sensitive adhesive sheet is preferably 50 to 100°C, more preferably 55°C or higher or 95°C or lower, and even more preferably 60°C or higher or 90°C or lower.
[0089] When the present pressure-sensitive adhesive sheet is heated, it is preferable to laminate two image display device components with the present pressure-sensitive adhesive sheet interposed therebetween, and then heat the laminate in a reduced pressure environment. By heating the laminate in a reduced pressure environment, it is possible to prevent air bubbles or foreign matter from being mixed into the pressure-sensitive adhesive sheet after lamination.
[0090] (Secondary pasting process) In the secondary adhesion process, the adhesive sheet is irradiated with light including light having a wavelength in the visible light range, preferably light having substantially no light having a wavelength of 380 nm or less, i.e., visible light, from the outside of at least one of the image display device constituent members through the image display device constituent member, to photocrosslink and harden the adhesive sheet.
[0091] By photocrosslinking in this manner, the pressure-sensitive adhesive sheet can be firmly crosslinked, and therefore can have adhesive strength and cohesive strength sufficient to withstand the gas pressure of outgassing generated from components of an image display device such as a protective panel, etc. Furthermore, since the pressure-sensitive adhesive sheet has ultraviolet absorbing properties, it is possible to suppress the deterioration of the pressure-sensitive adhesive sheet itself and the components of the image display device due to ultraviolet rays.
[0092] When irradiating with visible light, it is preferable to irradiate with visible light that does not substantially contain light with a wavelength in the ultraviolet region, for example, light with a wavelength of less than 365 nm. Here, "substantially free of light with wavelengths of less than 365 nm" means that the emission intensity of light with wavelengths of less than 365 nm is less than 1 mW / cm 2 It means less than.
[0093] As a method of irradiating visible light that does not contain light with wavelengths in the ultraviolet region, as described above, a light source that emits only visible light that does not contain light with wavelengths in the ultraviolet region may be used. Examples of light sources that emit only visible light include fluorescent lamps, LEDs, organic EL, and inorganic EL. Alternatively, the adhesive composition may be irradiated through a filter that does not transmit light having wavelengths in the ultraviolet region. For example, the adhesive composition may be irradiated with visible light through a filter having a light transmittance of less than 10% at 380 nm and a light transmittance of 60% or more at 405 nm, using a light-emitting lamp such as a high-pressure mercury lamp, a metal halide lamp, a xenon arc lamp, or a carbon arc lamp that also emits light having wavelengths in the ultraviolet region, or sunlight, as a light source. The filter may be a release film constituting the present pressure-sensitive adhesive sheet laminate, or a surface protection film to be laminated on the surface of the present pressure-sensitive adhesive sheet laminate.
[0094] In order to adjust the degree of visible light crosslinking, in addition to controlling the amount of visible light irradiation, it is also possible to adjust the degree of visible light crosslinking by irradiating visible light through the above-mentioned filter, thereby partially blocking the transmission of visible light.
[0095] <Explanation of terms, etc.> In addition, a "sheet" is generally defined in the JIS as a thin, flat product whose thickness is small relative to its length and width, and a "film" is generally defined as a thin, flat product whose thickness is extremely small compared to its length and width and whose maximum thickness is arbitrarily limited, and which is usually supplied in the form of a roll (Japanese Industrial Standard JISK6900). However, the boundary between a sheet and a film is unclear, and since there is no need to distinguish between the two in the present invention, in the context of the present invention, when it is referred to as a "film," it is intended to include a "sheet," and when it is referred to as a "sheet," it is intended to include a "film." Furthermore, when the term "panel" is used, such as an image display panel or a protective panel, it encompasses a plate, a sheet, and a film.
[0096] In this specification, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0098] In this example, the integrated light quantities at wavelengths of 405 nm and 365 nm were measured using an integrated actinometer (UIT-250, manufactured by Ushio Inc.).
[0099] [Example 1] As the (meth)acrylic copolymer (A), 15 parts by mass of polymethyl methacrylate macromonomer (Tg 80°C) having a number average molecular weight of 3000, 81 parts by mass of butyl acrylate, and 4 parts by mass of acrylic acid were added to 1 kg of a copolymer (A-1, mass average molecular weight 300,000) to which 100 g of glycerin dimethacrylate (NOF Corporation, Blenmar GMR) (B-1) as a crosslinking agent (B), 15 g of ESACURE KTO46 (C-1) (Lamberti) as a photopolymerization initiator (C), and 5 g of 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine (BASF, Tinuvin 1577) (D-1) as an ultraviolet absorber (D) were added and mixed uniformly to obtain a pressure-sensitive adhesive composition 1. The absorption coefficient of the photoinitiator (C-1) at 405 nm is 7.4 × 10 1 (mL / (g cm)).
[0100] Next, the adhesive composition 1 was formed into a sheet having a thickness of 100 μm on a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Inc., Diafoil MRV, thickness 100 μm), and then covered with a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Inc., Diafoil MRQ, thickness 75 μm) to produce an adhesive sheet laminate 1.
[0101] [Example 2] As the (meth)acrylic copolymer (A), 10 parts by mass of polymethyl methacrylate macromonomer (Tg 55 ° C) having a number average molecular weight of 1400 and 90 parts by mass of 2-ethylhexyl acrylate (Tg: -70 ° C) were randomly copolymerized to obtain 1 kg of acrylic graft copolymer (A-2) (weight average molecular weight: 230,000), 50 g of tricyclodecane dimethacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: DCP) (B-2) as the crosslinking agent (B), 15 g of Irgacure 369 (C-2) (manufactured by BASF) as the photopolymerization initiator (C), and 20 g of 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (manufactured by Johoku Chemical Co., Ltd., JF-80) (D-2) as the ultraviolet absorber (D) were uniformly mixed to prepare an adhesive resin composition 2.
[0102] Next, the adhesive composition 4 was applied to a thickness of 100 μm onto a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Inc., Diafoil MRV, thickness 100 μm), and then covered with a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Inc., Diafoil MRQ, thickness 75 μm) to produce an adhesive sheet laminate 2. The absorption coefficient of the photoinitiator (C-2) at 405 nm is 1.6 × 10 2 (mL / (g cm)).
[0103] [Example 3] As the (meth)acrylic copolymer (A), 76 parts by mass of 2-ethylhexyl acrylate, 20 parts by mass of vinyl acetate, and 4 parts by mass of acrylic acid (A-3, mass average molecular weight 400,000) were added to 1 kg of the copolymer, and 200 g of propoxylated pentaerythritol tetraacrylate (ATM-4P, manufactured by Shin-Nakamura Chemical Co., Ltd.) (B-3) as the crosslinking agent (B), 7 g of Irgacure 819 (C-3) (manufactured by BASF) as the photopolymerization initiator (C), and 10 g of 2,2'-dihydroxy-4-methoxybenzophenone (Kemisorb111, manufactured by Chemipro Chemical Co., Ltd.) (D-3) as the ultraviolet absorber (D) were added and mixed uniformly to obtain a pressure-sensitive adhesive composition 3. The absorption coefficient of the photoinitiator (C-3) at 405 nm is 9.0×10 2 (mL / (g cm)).
[0104] The adhesive resin composition 3 was sandwiched between two peel-treated polyethylene terephthalate films (Diafoil MRF, manufactured by Mitsubishi Plastics, Inc., thickness 75 μm / Diafoil MRT, manufactured by Mitsubishi Plastics, Inc., thickness 38 μm) and shaped into a sheet having a thickness of 100 μm to prepare an intermediate layer sheet (α).
[0105] To 1 kg of a pressure-sensitive adhesive solution (SK Dyne 1882, manufactured by Soken Chemical Industries, Ltd., solid content concentration approximately 17%) made of a commercially available acrylic copolymer (A-4, mass average molecular weight 1.3 million), 1.85 g of L-45 (B-5) (manufactured by Soken Chemical Industries, Ltd.) as an isocyanate-based crosslinking agent and 0.5 g of E-5XM (B-6) (manufactured by Soken Chemical Industries, Ltd.) as an epoxy-based crosslinking agent were added to prepare pressure-sensitive adhesive composition 4. The adhesive layer coating liquid was applied onto a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRV, thickness 100 μm) so that the film thickness after drying would be 20 to 30 μm, and then dried for 5 minutes at 80° C. This was aged at 23° C. for 7 days to react with the crosslinking agent, and a sheet for adhesive layer (β) was prepared. Furthermore, the above-mentioned adhesive layer coating liquid was similarly applied to a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRQ, thickness 75 μm) so that the adhesive composition 4 had a film thickness after drying of 20 to 30 μm, and then dried for 5 minutes at 80° C. This was aged for 7 days at 23° C. to react with the crosslinking agent, thereby preparing an adhesive layer sheet (β').
[0106] The PET films on both sides of the intermediate layer resin sheet (α) were sequentially peeled off and removed, and the adhesive surfaces of the adhesive layer resin sheets (β) and (β') were sequentially bonded to both surfaces of the intermediate layer sheet (α) to produce a laminate (thickness 150 μm) consisting of (β) / (α) / (β').
[0107] Through the PET film remaining on the surfaces of (β) and (β'), the integrated light intensity of 365 nm is 1000 mJ / cm 2 , the integrated light intensity at a wavelength of 405 nm is 1400 mJ / cm 2 The intermediate layer resin sheet (α) was photocrosslinked by irradiating it with light from a high pressure mercury lamp so that the sheet became oriented perpendicular to the sheet surface, thereby producing a pressure-sensitive adhesive sheet laminate 3.
[0108] [Example 4] Adhesive sheet laminate 4 was produced in the same manner as in Example 1, except that a release film made of a PET film (thickness 100 μm) containing an ultraviolet absorber and coated with a silicone release agent was used instead of a release-treated polyethylene terephthalate film (Diafoil MRV, thickness 100 μm).
[0109] [Example 5] The weak adhesive layer surface of a surface protection film consisting of a weak adhesive layer (5 μm) / polyethylene terephthalate film (25 μm) / ultraviolet absorbing layer (3 μm) was laminated on the surface of the polyethylene terephthalate film (Diafoil MRV, thickness 100 μm) of the adhesive sheet laminate prepared in Example 1, to prepare adhesive sheet laminate 5 consisting of a release film / adhesive sheet / release film / surface protection film structure.
[0110] [Comparative Example 1] A pressure-sensitive adhesive sheet laminate 6 was produced in the same manner as in Example 1, except that 15 g of ESACURE TZT (C-5) was added as the photopolymerization initiator instead of ESACURE KTO46 (C-1). The absorption coefficient of the photopolymerization initiator (C-5) at 405 nm was less than 10 (mL / (g·cm)), which was too low to measure.
[0111] [Comparative Example 2] A pressure-sensitive adhesive sheet laminate 7 was prepared in the same manner as in Example 2, except that the ultraviolet absorber (D-2) was not added.
[0112] [Comparative Example 3] To 1 kg of adhesive solution (Soken Chemical Industries, Ltd., SK Dyne 1882, solids concentration approximately 17%) consisting of a commercially available acrylic copolymer (A-4, mass average molecular weight 1.3 million), 1.85 g of L-45 (B-5) (Soken Chemical Industries, Ltd.) as an isocyanate crosslinking agent, 0.5 g of E-5XM (B-6) (Soken Chemical Industries, Ltd.) as an epoxy crosslinking agent, and 10 g of 2,2'-dihydroxy-4-methoxybenzophenone (Kemisorb111, Chemipro Chemical Industries, Ltd.) (D-3) as an ultraviolet absorber (D) were added and mixed uniformly to prepare adhesive composition 7.
[0113] Next, the adhesive composition was applied onto a release-treated polyethylene terephthalate film (Mitsubishi Chemicals, Diafoil MRV, thickness 100 μm) so that the thickness after drying would be 50 μm, and then dried at 80° C. for 5 minutes to obtain a sheet-like adhesive composition 7 having a thickness of 50 μm. The adhesive composition was similarly applied to a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRQ, thickness 75 μm) so that the thickness after drying would be 50 μm, and then dried at 80° C. for 5 minutes to obtain a sheet-like adhesive composition 7 having a thickness of 50 μm. These were laminated to a thickness of 100 μm, and then covered with a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRQ, thickness 75 μm). This was aged at room temperature (23° C.) for 7 days to react with the crosslinking agent, and an adhesive sheet laminate 8 was produced.
[0114] <Evaluation> [Optical properties] The PET films on both sides of the adhesive sheet laminates produced in the Examples and Comparative Examples were sequentially peeled off, and the adhesive sheets were sandwiched between two sheets of soda lime glass (thickness 0.5 mm) and attached, and then autoclaved (70°C, gauge pressure 0.2 MPa, 20 minutes) for finish attachment. For the adhesive sheet laminates 1, 2, 4, 5, 6, and 7, a high-pressure mercury lamp with a UV cut filter was used to illuminate the laminate with an integrated light intensity of 3000 mJ / cm at a wavelength of 405 nm. 2 A sample for evaluating optical properties was prepared by irradiating the sample with light so as to obtain the following:
[0115] The light transmittance of the prepared test piece in the wavelength range of 360 to 430 nm was measured using a spectrophotometer (manufactured by Shimadzu Corporation; device name "UV2450"). A sample with a light transmittance of less than 50% at 380 nm was judged to have UV absorbency of "○ (good)," and a sample with a light transmittance of 50% or more was judged to have UV absorbency of "× (poor)." The results are shown in Table 1.
[0116] [Adhesive strength] For the pressure-sensitive adhesive sheets produced in the Examples and Comparative Examples, one release film was peeled off, and a polyethylene terephthalate film (manufactured by Toyobo Co., Ltd.; product name "Cosmoshine A4300", thickness 100 μm) was roll-pressed onto the backing film using a hand roller. This was cut into strips of 10 mm width x 100 mm length, and the remaining release film was peeled off to expose the adhesive surface, which was then roll-pressed onto soda-lime glass using a hand roller. After finish-pasting by autoclaving (70°C, gauge pressure 0.2 MPa, 20 minutes), pressure-sensitive adhesive sheet laminates 1, 2, 4, 5, 6, and 7 were exposed using a high-pressure mercury lamp with a UV-cut filter, with an integrated light intensity of 3000 mJ / cm at a wavelength of 405 nm. 2 , the integrated light intensity at a wavelength of 365 nm is 5 mJ / cm 2 Visible light was irradiated as follows to prepare a sample for measuring adhesive strength.
[0117] The adhesive sheet was peeled off from the glass while pulling the backing film at an angle of 180° at a peeling speed of 60 mm / min, and the tensile strength was measured with a load cell to determine the 180° peel strength (N / cm) of the adhesive sheet to the glass, which is shown as "glass adhesion strength" in Table 1. The results are shown in Table 1.
[0118] [Bump absorption] A 20 μm thick print was applied to the peripheral portion (3 mm on the long side, 15 mm on the short side) of a 58 mm x 110 mm x 0.8 mm thick glass plate to prepare a glass plate 1 with a printed step and an opening of 52 mm x 80 mm. In addition, a 10 μm thick print was applied to the peripheral portion (3 mm on the long side, 15 mm on the short side) of a 58 mm x 110 mm x 0.8 mm thick glass plate to prepare a glass plate 2 with a printed step and an opening of 52 mm x 80 mm. The release film on one side of the pressure-sensitive adhesive sheet laminate was peeled off, and the laminate was then roll-bonded to a soda-lime glass sheet measuring 54 mm×82 mm and 0.5 mm thick. Next, the remaining release film was peeled off, and the adhesive surface was pressed and bonded to the printed surfaces of the printed stepped glass plates 1 and 2 using a vacuum press so that the four sides of the adhesive surface overlapped the printed stepped areas (absolute pressure 5 kPa, temperature 70°C, press pressure 0.04 MPa), and then autoclaved (70°C, gauge pressure 0.2 MPa, 20 minutes) for finish bonding. For the adhesive sheet laminates 1, 2, 4, 5, 6, and 7, a high-pressure mercury lamp with a UV-cut filter was used from the printed glass side, with an accumulated light intensity of 3000 mJ / cm at a wavelength of 405 nm. 2 Thus, a sample for evaluation was prepared.
[0119] For the evaluation samples, the glass plate 1 with a 20 μm printed step was judged to have excellent unevenness absorption if it could be bonded without any air bubbles near the step, the glass plate 2 with a 10 μm printed step was judged to have good unevenness absorption if it could be bonded without any air bubbles near the step, and the glass plates 1 and 2 with printed steps were judged to have poor unevenness absorption if air bubbles were found near the step. The results are shown in Table 1.
[0120] [Heat resistance] The release film on one side of the pressure-sensitive adhesive sheets prepared in the Examples and Comparative Examples was peeled off, and a COP film (100 μm, manufactured by Zeon Corporation) was attached to the exposed surface with a hand roller. Next, the pressure-sensitive adhesive sheet was cut into a size of 50 mm × 80 mm, and the remaining release film was peeled off. The sheet was then attached to a 0.5 mm-thick soda lime glass with a hand roller, and autoclaved (temperature 80°C, pressure 0.4 MPa, 30 minutes). For pressure-sensitive adhesive sheet laminates 1, 2, 4, 5, 6, and 7, a high-pressure mercury lamp was used through a UV-cut filter to illuminate the COP surface with an integrated light intensity of 3000 mJ / cm at a wavelength of 405 nm. 2 Thus, a sample for evaluation was prepared.
[0121] The evaluation samples were aged at 85°C for 6 hours, and those that showed no change in appearance, such as foaming, were judged as having heat resistance of "○ (good)", and those that showed foaming or peeling were judged as having heat resistance of "× (poor)". The results are shown in Table 1.
[0122] [Light resistance] One release film of the adhesive sheet laminate was peeled off, and the laminate was roll-bonded to a 150 mm × 200 mm, 2 mm thick soda lime glass. Next, the remaining release film was peeled off, and the exposed adhesive surface was roll-bonded to a 150 mm × 200 mm, 2 mm thick soda lime glass, and autoclaved (temperature 80°C, pressure 0.4 MPa, 30 minutes). For the pressure-sensitive adhesive sheet laminates 1, 2, 4, 5, 6, and 7, a high-pressure mercury lamp was used, and the integrated light amount at a wavelength of 405 nm was 3000 mJ / cm 2 Thus, a sample for evaluation was prepared.
[0123] The evaluation samples were irradiated with ultraviolet light for 24 hours using a xenon light resistance tester (Suntest CPS, manufactured by Atlas Co., Ltd.), and those that did not show any lifting or peeling on the adhesive sheet were judged as having light resistance of "○ (good)", and those that showed lifting or peeling were judged as having light resistance of "× (poor)". The results are shown in Table 1.
[0124] [Table 1]
[0125] The light transmittance in the wavelength range of 380 to 450 nm was measured using a spectrophotometer (Shimadzu Corporation; device name "UV2450") for the release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRV, thickness 100 μm) used in Example 1, the release film made of a PET film (thickness 100 μm) containing an ultraviolet absorber and coated with a silicone release agent used in Example 4, and the surface protection film used in Example 5. The results are shown in Table 2.
[0126] For the adhesive sheet laminate 1, adhesive sheet laminate 4, and adhesive sheet laminate 5, a release-treated polyethylene terephthalate film (Mitsubishi Plastics, Diafoil MRV, thickness 100 μm), a release film coated with a silicone release agent on a PET film (thickness 100 μm) containing an ultraviolet absorbing agent used in Example 4, and a surface protective film were placed on the upward side. The film side was irradiated with light from a fluorescent lamp (illuminance 1100 Lx) for 7 days. The accumulated light amount of the irradiated light at a wavelength of 405 nm was approximately 43 J / cm. 2 The integrated light quantity at a wavelength of 365 nm is approximately 1 mJ / cm 2 The following were not measurable.
[0127] The gel fraction of the adhesive was determined by the following method for the adhesive sheet laminates 1 and 4 before and after the light irradiation treatment. The results are shown in Table 2.
[0128] 1) The pressure-sensitive adhesive composition is weighed (W1) and wrapped in a pre-weighed SUS mesh (W0). 2) Immerse the above SUS mesh in 100 mL of ethyl acetate for 24 hours. 3) Remove the SUS mesh and dry it at 75℃ for 4.5 hours. 4) The weight (W2) after drying is determined, and the gel fraction of the pressure-sensitive adhesive composition is calculated using the following formula. Gel fraction (%) = 100 × (W2-W0) / W1
[0129] Regarding storage stability, samples in which the gel fraction changed by less than 5 points before and after exposure to fluorescent light were rated as "○ (good)," and samples in which the gel fraction increased by 5 points or more after exposure to light were rated as "× (poor)." The results are shown in Table 2.
[0130] [Table 2]
[0131] The pressure-sensitive adhesive sheet laminates of Examples 1 to 5 not only had excellent ultraviolet absorbing performance, but also had excellent quality by achieving both the ability to absorb irregularities during lamination and reliability after lamination of members. In contrast, Comparative Example 1 used a photopolymerization initiator with an absorption coefficient of less than 10 mL / (g cm) at a wavelength of 405 nm, i.e., a photopolymerization initiator with an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm was not used. As a result, the adhesive did not harden even when irradiated with light, and no adhesive strength or reliability after secondary attachment was obtained. Comparative Example 2 did not contain the ultraviolet absorber (D) and could not obtain ultraviolet absorbing performance, and therefore, foaming of the pressure-sensitive adhesive sheet was observed in the light resistance test, and the lamination reliability was poor. Comparative Example 3 is a pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive composition is crosslinked by thermal crosslinking. Since it does not have a photocurable layer, it was poor in terms of unevenness absorption during application.
[0132] In addition, a PET film containing an ultraviolet absorber was used as the release film in Example 4. This made it possible to suppress the progress of the photocuring reaction of the adhesive composition before bonding to a member, and to obtain an adhesive sheet laminate with excellent storage stability.
[0133] In Example 5, a surface protection film having an ultraviolet absorbing layer was laminated on the surface of the release film, which prevented the photocuring reaction of the adhesive composition from progressing before the adhesive composition was attached to a member, and provided an adhesive sheet laminate with excellent storage stability.
Claims
1. The adhesive layer comprises a single layer or two or more layers formed from an adhesive resin composition containing a (meth)acrylic copolymer (A), a crosslinking agent (B), a photopolymerization initiator (C) having an absorption coefficient of 10 mL / (g cm) or more at a wavelength of 405 nm, and an ultraviolet absorber (D); The ultraviolet absorber (D) is contained in an amount of 0.1 parts by mass or more and 3 parts by mass or less based on 100 parts by mass of the (meth)acrylic copolymer (A), The crosslinking agent (B) contains at least a polyfunctional (meth)acrylate, and The adhesive layer is a photocurable, transparent, double-sided adhesive sheet (excluding those containing a multi-acrylate oligomer having 2-5 acrylate functional groups).
2. A transparent double-sided adhesive sheet as described in claim 1, wherein the multifunctional (meth)acrylate is a multifunctional (meth)acrylic acid ester monomer.
3. A transparent double-sided adhesive sheet as described in claim 1 or 2, wherein the adhesive layer has the curing properties to be cured by visible light.
4. A transparent double-sided adhesive sheet described in any one of claims 1 to 3, wherein the mass average molecular weight of the (meth)acrylic copolymer (A) is 100,000 to 1,500,000.
5. A transparent double-sided adhesive sheet described in any one of claims 1 to 4, characterized in that the ultraviolet absorber (D) has one or more structures selected from the group consisting of a benzotriazole structure, a triazine structure, and a benzophenone structure.
6. A transparent double-sided adhesive sheet described in any one of claims 1 to 5, characterized in that it contains 25 to 400 parts by mass of the ultraviolet absorber (D) per 100 parts by mass of the photopolymerization initiator (C).
7. The (meth)acrylic copolymer (A) contains an acrylic copolymer consisting of a graft copolymer having a macromonomer as a branch component, The crosslinking agent (B) contains a polyfunctional (meth)acrylic acid ester monomer, The photopolymerization initiator (C) contains a cleavage-type photopolymerization initiator, 7. The transparent double-sided pressure-sensitive adhesive sheet according to claim 1, characterized in that the ultraviolet absorber (D) contains an ultraviolet absorber having a benzotriazole structure or a benzophenone structure.
8. The transparent double-sided adhesive sheet according to any one of claims 1 to 7, wherein the adhesive resin composition exhibits adhesiveness at room temperature (20°C) even in an uncrosslinked state, and has the property of softening or flowing when heated to a temperature of 50 to 100°C.
9. 9. A pressure-sensitive adhesive sheet laminate comprising the transparent double-sided pressure-sensitive adhesive sheet according to claim 1 and a release film laminated thereon.
10. 10. The pressure-sensitive adhesive sheet laminate according to claim 9, wherein at least one of the release films has a light transmittance of 40% or less for light having a wavelength of 410 nm or less.
11. 10. The pressure-sensitive adhesive sheet laminate according to claim 9, comprising a surface protective film having a light transmittance of 40% or less for light having a wavelength of 410 nm or less laminated on the surface of at least one of the release films.
12. 9. A laminate for use in constructing an image display device, comprising two constituent members laminated together with the transparent double-sided pressure-sensitive adhesive sheet according to claim 1 interposed therebetween.
13. The laminate for use in constructing an image display device according to claim 12, characterized in that the image display device component is a laminate consisting of any one or a combination of two or more of the group consisting of a touch sensor, an image display panel, a surface protection panel, and a polarizing film.
14. An image display device constructed using the laminate for constituting an image display device according to claim 12 or 13.
Citation Information
Patent Citations
JP1974071529A
Ultraviolet curable adhesive sheet
JP2000104026A
Curable pressure sensitive adhesive composition
JP2006512442A
Gas barrier laminated film
JP2012121255A
Transparent double-sided adhesive sheet and image display device
JP2015157884A